GENETIC VARIABILITY STUDIES FOR YIELD AND WITHIN BOLL YIELD COMPONENTS IN COTTON (GOSSYPIUM HIRSUTUM L.) - NADEEM, A; SHAKEEL, A; IMTIAZ, M; NASIR, B; KHALID, MN; AMJAD, I (Biological and Clinical Sciences Research Journal, 2022)
Cotton is a prominent fiber crop all across the world, including Pakistan.. But the production of cotton is relatively low in Pakistan. As boll is the basic determinant for yield in cotton crop, the study on within boll yield parameters was carried out using twenty exotic accessions of cotton to check their variability for within boll yield components. The experiment was performed at the research area of the department of Plant Breeding and Genetics, University of Agriculture, Faisalabad. The genotypes were seeded in three replications following randomized complete block design (RCBD). At maturity, data were collected for different within boll yield parameters. The analysis of variance showed significant results for nine out of eleven parameters studied. Principal component analysis revealed that genotype ZB-18015 showed maximum variation with respect to all parameters because it was at a maximum distance from the origin followed by genotype ZB-18020, ZB-18019 and ZB-18018 respectively. Cluster analysis identified particular groups of genotypes that were having maximum similarity with each other. In addition, the findings of the current study revealed the potential of different accessions of cotton for development of high yielding varieties. This information may be used to devise breeding strategies in the future to enhance cotton production and variety development.